Penguatan Storytelling Dalam Format Digital Untuk Wisata Sejarah Di Museum Pusat TNI-AU Dirgantara Mandala - Pitaya; Ghifari Yuristiadhi Masyhari Makasi (STIE Pariwisata API Yogyakarta, 2022)
The Indonesian Air Force Dirgantara Mandala Central Museum is a very special tourist attraction in Yogyakarta. This museum is a representative place to study the history of the struggle of the Indonesian people in the field of aerospace. Not only the main collection of weapons system and various other historical relics, the TNI-AU Dirgantara Mandala Central Museum also stores various patriotic and heroic stories from historical actors. Each museum collection that has its own story will be very interesting if it is expressed in the right storytelling scheme. The study focuses on how to include storytelling content related to the stories of the sky knights and the main weapon system. The method used is observation and literacy studies as well as scrutiny of documentation photos which is then recorded digitally to obtain a storytelling format model that is easy to observe repeatedly. The results show that digital storytelling may represent a new experience for tourists' understanding of museum collections. One important thing is that this storytelling format can be easily downloaded, duplicated, repeated to get information that is not only accurate but also convenient in understanding what has happened in the aerospace history of the Indonesian nation.